Drivers in the implementation of sustainable construction management among main contractors - Nur Syamimi, Zulkefli; Leo, Yu Ling (2017)
Sustainability practice has been introduced world widely across many industries including construction sector with the aims to balance between the development of country and our Mother Nature. However, despite having various benefits, this practice has not been widely implemented. The situation has resulted climate change or global warming to became more serious compared to what happen previously. Therefore, this research has been conducted to identify what drive the organization to implement sustainable construction in their projects. Comprehensive review of pertinent literature and questionnaire survey were used to collect the research data. A total of 339 G7 contractors who registered under CIDB located in Johor Bahru have been selected as respondents with only 53.10% of them respond to the survey. All the data were analyzed by using Statistical Package for the Social Science (SPSS). Findings from the research explain that introduction series of tax incentives is the most significant driving factor for contractors to implement sustainable practices in construction industry. Recommendations have been proposed in this research which hopefully may help to improve numbers of sustainable construction management implementation.